The components of the female athlete triad do not identify all physically active females at risk - Burrows, M.; Shepherd, H.; Bird, S.; Macleod, K.; Ward, B. (Journal of Sports Sciences, 2007)
The purpose of the present study was to assess the effectiveness of the triad components (amenorrhoea, disordered eating, and osteoporosis) in identifying physically active women at risk of long-term health problems. Eighty-two females (mean age 31.1 years, s = 6.7; body mass 58.4 kg, s = 6.6; stature 1.65 m, s = 0.06) completed training, menstrual, and dietary questionnaires. Bone mineral density and size-adjusted bone mineral density were assessed at the femoral neck and lumbar spine using dual energy X-ray absorptiometry. Seventy-eight percent of participants were eumenorrhoeic, 20% were oligomenorrhoeic, and 2% were amenorrhoeic. Thirty-six percent and 55% reported disordered eating practices in the present and past respectively. Eighty-one percent, 17%, and 2% were classified as normal, osteopaenic, and osteoporotic at the femoral neck respectively; 92% were normal, 7% osteopaenic, and 1% osteoporotic at the lumbar spine. No significant differences in femoral neck size-adjusted bone mineral density were observed between eumenorrhoeic and oligo/amenorrhoeic participants (F2,80 = 0.119, P = 0.73); eumenorrhoeic participants had significantly greater lumbar spine size-adjusted bone mineral density (F2,80 = 9.79, P = 0.003). Disordered eating participants had significantly lower femoral neck size-adjusted bone mineral density than those reporting no disordered eating (F2,80 = 13.816, P = 0.000). Twenty-two percent of participants fulfilled triad criteria, while 55% were "at risk" of long-term health problems. An accumulation of conditions resulted in lower lumbar spine size-adjusted bone mineral density (F1,80 = 6.074, P = 0.004). The current triad components do not identify all women "at risk" and more appropriate criteria such as exercise-related menstrual alterations, disordered eating, and osteopaenia are suggested.